2021
DOI: 10.1002/pad.1956
|View full text |Cite
|
Sign up to set email alerts
|

The institutionalization and effectiveness of transnational policy transfer: The China–Singapore Suzhou Industrial Park as a case study

Abstract: Transnational policy transfer through cross-border government-to-government collaboration projects has been widely adopted as a tool to facilitate economic growth, especially by developing countries. Why did some transnational projects of policy transfer succeed while others fail? What are the facilitating and constraining factors in shaping their fates? What are their theoretical and policy implications for public administration and economic development in a globalizing world? This article examines the case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Various public enterprises have been involved in the transfer of policies for special economic zones and industrial parks in the region. For example, Singapore involved its public enterprises to set up the China‐Singapore Suzhou Industrial Park as a way to export its economic development model to China, facilitated by high level between ministry officials (Inkpen & Pien, 2006; Liu & Wang, 2021). Similarly, China and Malaysia involved both national and local government officials in setting up the Malaysia‐China Kuantan Industrial Park, which involved the state‐owned companies of both countries (Liang et al, 2021).…”
Section: Toward a Relational Framework Of Policy Transfermentioning
confidence: 99%
“…Various public enterprises have been involved in the transfer of policies for special economic zones and industrial parks in the region. For example, Singapore involved its public enterprises to set up the China‐Singapore Suzhou Industrial Park as a way to export its economic development model to China, facilitated by high level between ministry officials (Inkpen & Pien, 2006; Liu & Wang, 2021). Similarly, China and Malaysia involved both national and local government officials in setting up the Malaysia‐China Kuantan Industrial Park, which involved the state‐owned companies of both countries (Liang et al, 2021).…”
Section: Toward a Relational Framework Of Policy Transfermentioning
confidence: 99%
“…Institutionalization is a key characteristic of China’s recent engagement with the Global South. The effectiveness of transnational policy transfer is contingent on institutionalization – defined by Samuel Huntington as ‘the process by which organizations and procedures acquire value and stability’ (cited in Liu & Wang, 2021) at both ends of the exchange. Since 2000, China has either set up or actively participated in multilateral mechanisms and fora specifically related to the Global South.…”
Section: The Global South and The Brimentioning
confidence: 99%
“…Although they are considered innovative urban districts and the new direction of restructuring has attracted emerging attention from scholars, its characteristics and mechanism systematization still need further discussion [21,[63][64][65][66]. Secondly, in terms of research fields, many studies are biased toward focusing on, and reinforcing knowledge of, their own field (albeit with reference to other fields) [21,[63][64][65][66][67][68][69][70][71]. This means that the fact that development zones themselves have become a complete system for restructuring China's development approach in the post-reform era, including different dimensions of policies and actions, has been downplayed.…”
Section: Literature Review: Towards a More Holistic And Dynamic Under...mentioning
confidence: 99%
“…In the case studies, two cases that have often been discussed in previous research were chosen and studied again, and the shortcomings of existing research were revealed to clarify the mutual relationship and common development laws governing the complex impetus of the restructuring process. Although the existing literature plays an important role in our understanding of development zones in different dimensions, such as systems, industries and land, development zones in fact reflect a holistic process that highlights the importance and significance of adopting the conceptual framework [22,[67][68][69][70][71][72]. If this approach is not taken, research in sub-fields will lead to the misinterpretation or misunderstanding of development zones and the restructuring processes that govern them.…”
Section: Zone Level: Forming a Holistic And Dynamic Conceptual Framew...mentioning
confidence: 99%